Single diode circuit model of photovoltaic (PV) cell: load current estimator / Nor Azni Shahari ... [et al.] - Shahari, Nor Azni; Mohamad Azraei, Farah Atikah; Rosli, Nurul Nabilah; lzaham, Siti Najwa (UiTM Cawangan Negeri Sembilan, 2021)
With the increasing search for new technologies that improve the utilization of existing renewable energy sources, the use of solar energy is spreading increasingly. There are numerous ways to use solar energy to generate electricity. This generation is used here by means of photovoltaic cells. A photovoltaic (PV) cell is an energy harvesting technology, that converts solar energy into useful electricity through a process called the photovoltaic effect. This cell can be connected in series, parallel or mixed form. The electrical model with a diode is the most used, as well as two resistors’ series Rs and shunt Rp respectively associated with the circuit. Studies with photovoltaic cells in some situations can't be performed by many iniluences, such as rain. Therefore, it's necessary to use a model that faithfully represents a cell's features so that studies can be performed in the laboratory and a mathematical model is used to make such representation. This derived mathematical model for PV cells is implemented in MATLAB software that uses a numerical method to estimate the load current.